Differential Effects of Purinergic Signaling in Gastric Cancer-Derived Cells Through P2Y and P2X Receptors - Hevia, María José; Castro, Patricio; Pinto, Katherine; Reyna-Jeldes, Mauricio; Rodríguez-Tirado, Felipe; Robles-Planells, Claudia; Ramírez-Rivera, Sebastián; Madariaga, Juan Andrés; Gutierrez, Felipe; López, Javier; Barra, Marcelo; De la Fuente-Ortega, Erwin; et al. (Frontiers in Pharmacology, 2019)
Gastric Cancer (GC) is the one of the most prevalent and one of the leading causes of cancer-induced deaths. Previously, we have found that the purinergic P2Y2 receptor (P2Y2R) expression is increased in GC samples as compared to adjacent healthy mucosa taken from GC-diagnosed patients. In this work, we studied in detail the purinergic signaling in the gastric adenocarcinoma-derived cell lines, AGS, MKN-45 and MKN-74 and compared to the non-tumoral epithelial cell line, GES-1. In GC-derived cells, we detected the expression of several purinergic receptors, and we found important differences compared to GES-1 cells. Functional studies revealed a strong contribution of P2Y2Rs in intracellular calcium increases, elicited by ATP, UTP and the P2Y2R-agonist MRS2768. Responses were preserved in the absence of extracellular calcium and inhibited by P2Y2R antagonists. In GES-1 cells, ATP and UTP induced similar responses and the combination of P2X and P2Y receptor antagonists were able to block these responses. Proliferation studies showed that ATP regulates AGS and MKN-74 cells in a biphasic manner, increasing cell proliferation at 10 -100 μM, but inhibiting at 300 μM ATP. On the other hand, 1-300 μM UTP, a P2Y2R-agonist, increased concentration-dependently cell proliferation. The effects of UTP and ATP were prevented by wide-range and specific purinergic antagonists. In contrast in GES-1 cells ATP only decreased cell-proliferation in a concentration-dependent manner and UTP had no effect. Notably, the sole application of purinergic antagonists was sufficient to change the basal proliferation of AGS cells, indicating that nucleotides released by the cells can act as paracrine/autocrine signals. Finally, in tumor-derived biopsies, we found an increase of P2Y2R and a decrease P2X4R expression; however, we found high variability between 7 different biopsies and their respective adjacent healthy gastric mucosa. Although these differences, we found a correlation between the level of expression of P2Y2R and P2X4R and survival of gastric cancer patients. Taken together, these results demonstrate the involvement of different purinergic receptors and signaling in GC, and the pattern of expression changes in tumoral cells, and this change probably directs ATP and nucleotide signaling from anti-proliferative effects in healthy tissues to proliferative effects in cancer.